Generalized lymphatic anomaly successfully treated with long‐term, low‐dose sirolimus. Issue 4 (26th March 2018) - Dvorakova, Veronika; Rea, David; O'Regan, Grainne M.; Irvine, Alan D.
Abstract: Generalized lymphatic anomaly is a rare, complex, lymphatic anomaly generally involving soft tissues, spleen, and bones. It can lead to focal skeletal fragility and pathologic effusions. A recent prospective trial of sirolimus for complicated vascular anomalies showed partial response in seven patients with generalized lymphatic anomaly treated with sirolimus with a target trough level of 10‐15 ng/mL for 1 year (Adams et al). We describe successful treatment of generalized lymphatic anomaly with a lower‐dose, long‐term course of sirolimus.